2017
DOI: 10.1126/sciimmunol.aan1457
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for potent antibody-mediated neutralization of human cytomegalovirus

Abstract: Human cytomegalovirus (HCMV) is the leading viral cause of birth defects and organ transplant rejection. The HCMV gH/gL/UL128/UL130/UL131A complex (Pentamer) is the main target of humoral responses and thus a key vaccine candidate. We report two structures of Pentamer bound to human neutralizing antibodies, 8I21 and 9I6, at 3.0 and 5.9 Å resolution, respectively. The HCMV gH/gL architecture is similar to that of Epstein-Barr virus (EBV) except for amino-terminal extensions on both subunits. The extension of gL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 42 publications
5
91
0
Order By: Relevance
“…Over the past decade, the HCMV vaccine field has largely shifted its focus away from the elicitation of gB-specific antibody responses and towards the targeting of the gH/gL/UL128/UL130/UL131A pentameric complex (PC) because this protein construct was newly identified as a primary target of potent HCMV neutralizing antibodies (24, 43). Yet, it is important to recognize that the gB/MF59 vaccine platform, which did not include the PC, achieved approximately 50% vaccine efficacy in preventing primary HCMV infection in two phase II trials (14, 15) and demonstrated a protective benefit for transplant recipients (20) without the elicitation of potent neutralizing antibody responses (20, 25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, the HCMV vaccine field has largely shifted its focus away from the elicitation of gB-specific antibody responses and towards the targeting of the gH/gL/UL128/UL130/UL131A pentameric complex (PC) because this protein construct was newly identified as a primary target of potent HCMV neutralizing antibodies (24, 43). Yet, it is important to recognize that the gB/MF59 vaccine platform, which did not include the PC, achieved approximately 50% vaccine efficacy in preventing primary HCMV infection in two phase II trials (14, 15) and demonstrated a protective benefit for transplant recipients (20) without the elicitation of potent neutralizing antibody responses (20, 25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…Like gD, gp42 is a receptor binding protein for EBV and is considered a functional (albeit not structural) homologue of gD. Second, complexes of gH/gL with other viral proteins have been visualized for human cytomegalovirus (28,29). Third, when gB, gD, and gH/gL were swapped between HSV-1 and the closely related saimiriine herpesvirus 1 (SaHV-1), cell-cell fusion was observed only when gD and gH/gL were both from the same virus, suggesting that the two proteins interact with each other in a speciesspecific manner (19,20).…”
mentioning
confidence: 99%
“…The study of these nonhuman herpesviruses in their natural hosts or HHVs in humanized animal models could help to clarify the relevance of herpesvirus chemokines in the context of a natural viral infection. NOTE ADDED IN PROOF: While this review was in press, the structure of the gH/gL/UL128-UL130-UL131A pentamer was published [258]. This new structure resolves the controversies about the biochemistry and protein-protein interactions of this complex discussed in this review.…”
Section: Discussionmentioning
confidence: 90%